2021
DOI: 10.3390/v13081441
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Widespread Zika Transmission across the Philippines

Abstract: Zika virus (ZIKV) exposure across flavivirus-endemic countries, including the Philippines, remains largely unknown despite sporadic case reporting and environmental suitability for transmission. Using laboratory surveillance data from 2016, 997 serum samples were randomly selected from suspected dengue (DENV) case reports across the Philippines and assayed for serological markers of short-term (IgM) and long-term (IgG) ZIKV exposure. Using mixture models, we re-evaluated ZIKV IgM/G seroprevalence thresholds an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…The ZIKV outbreak in the Americas has drawn renewed interest in the epidemiology and transmission of ZIKV in other parts of the world (15). Several lines of evidence including documented Zika cases among travelers from Southeast Asia, retrospective analysis of archived samples, and enhanced surveillance suggested that ZIKV has been circulating at a low but sustained level in several countries in Southeast Asia including the Philippines [46][47][48][49][50][51][52]. Consistent with these reports, we found approximately 10% of the participants from the Philippines had previous ZIKV or ZIKV and DENV infections [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The ZIKV outbreak in the Americas has drawn renewed interest in the epidemiology and transmission of ZIKV in other parts of the world (15). Several lines of evidence including documented Zika cases among travelers from Southeast Asia, retrospective analysis of archived samples, and enhanced surveillance suggested that ZIKV has been circulating at a low but sustained level in several countries in Southeast Asia including the Philippines [46][47][48][49][50][51][52]. Consistent with these reports, we found approximately 10% of the participants from the Philippines had previous ZIKV or ZIKV and DENV infections [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some with elevated ELISA antibody response were negative for corresponding antibody RDTs. This trend could be attributed to ELISAs, yet not RDTs, cross-reacting with other flaviviruses including ZIKV which has shown to be potentially widespread across dengue-endemic countries [ 30 32 ]. It is now well established commercial DENV ELISAs cross-react with ZIKV [ 40 , 41 ] yet whether DENV antibody rapid tests cross-react with ZIKV remains poorly characterised and deserves further attention [ 25 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among active cases on disease day 3 to 5, individuals with IgG:IgM ratios above and below 0.45 were categorised as post-primary and primary respectively. As a consequence of previous findings [ 12 , 32 ], post-primary cases included current DENV infections with at least one previous flavivirus infection including DENV and or ZIKV. An overview of the reference DENV immune status classification is shown in S1 File .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations